(De)construyendo ilusiones. Cambios intergeneracionales y de género en las aspiraciones educativas y ocupacionales en las zonas rurales de Ayacucho - Mena Portocarrero, Magrith (2012)
To make a wish. Educational and occupational aspirations in two generations of rural children, in Ayacucho (Peru) This paper presents a genealogy of educational and occupational aspirations, based on the desires of two generations of rural children of Ayacucho. Taking the region’s recent turbulent and violent history into account, and other recent structural social changes, the research shows how the aspirations change between both generations, paying special attention to gender differences. Terciary education becomes the most wanted future, while peasant activities almost disappear from desired future lives; in addition, in poorer households girls keep higher aspirations than their male peers. Despite all this, hard evidence shows that tertiary education is rarely reached in Ayacucho, and women still have less opportunity to access and finish secondary and tertiary education. Therefore, this genealogy of desires not only should be seen as a social construction, but also as an expression of voice and agency, where social hierarchies are questioned.